EVALUATION OF KNOWLEDGE LEVEL AND APPROACHES IN TRAUMATIC DENTAL INJURIES AMONG DIFFERENT MEDICAL OCCUPATIONAL GROUPS - Şerife Özalp; Ayşenur Özbulur (Selcuk Dental Journal)
Background:Proper diagnosis and first intervention in dental trauma is of importance in terms of prognosis. The level of knowledge of pediatricians, emergency medicine physicians and dentists constitutes the most important step in carrying out this intervention. The aim of this study was to determine the level of knowledge of pediatricians, pediatric residents, emergency medicine specialists and dentists on dental traumas.Methods:A total of 103 people participated in this survey study conducted on pediatricians, emergency physicians and dentists serving in 10 different hospitals in Istanbul, and a survey including fourteen multiple-choice questions was prepared to determine the level of knowledge on the basic issues that are important for emergency intervention in trauma cases.Results:Of the participants, 55 % stated that the first aid training they received included dental trauma intervention, and 89 % answered the question of "Have you have ever encountered any dental trauma?" as "Yes". Particularly in avulsion cases, the knowledge level of the participants was found to be low in terms of treatment procedures related to tooth replacement.Conclusions:In this study, the knowledge of pediatricians, emergency physicians and dentists on dental trauma was evaluated, and according to the results of this survey, it was concluded that the issue of emergency interventions in dental traumas should be more emphasized in the training of these occupational groups.Keywords:Trauma, child, emergency treatment, dentistry